A Pedagogical Model in a Non-Formal Educational Context: The Museum Un Modelo Pedagógico en un Contexto No Formal: El Museo. - Mª Begoña Alfageme González; Nicolás Martínez Valcárcel (Arizona State University, 2007)
Our proposal is to present a model of educational planning for museums. The school cannot be assumed to render all the education that a person needs. Therefore other social institutions are called upon to complement a person?s training. We begin by justifying the interest of including non-formal education in this context. Subsequently, we focus our study on an educational model that can be used as a planning tool in museums, thus expanding its use as a formative institution as well. Nuestra propuesta se centra en presentar un modelo de planificación educativa para las instituciones museísticas. La escuela no puede asumir toda la educación que un sujeto necesita, de ahí que tengan que ser otras instituciones sociales las que ayuden a complementar su formación. Comenzamos justificando el interés de abarcar la educación no formal en este contexto, y terminamos profundizando en el estudio de un modelo de enseñanza que nos puede ayudar a planificar en los museos, potenciando, así, sus posibilidades de uso formativo.